Swiss Society for Research in Education – looking back at its 40-year history - Grossenbacher, Silvia (Swiss Journal of Educational Research, 2002)
Against the background of the institutional and research policy developments in the field of educational research, this article highlights aspects of the 40-year history of the Swiss Society for Research in Education (SSRE). Since it was founded in 1975, the Society has striven – not without a certain degree of self-criticism – to develop this multidisciplinary research area. The article outlines what the Society has done to raise the profile of this research area and to support researchers, the research policy priorities it has pursued, and how it has encouraged competence building and the promotion of young researchers. Finally, it pays tribute to the Society’s discussion forum, the «Schweizerische Zeitschrift für Bildungswissenschaften».